Synechococcus sp. and Pseudanabaena sp. cell culture biogenesis towards pH, period of time and bio-concentration factor (BCF) - Othman, Rashidi; Shaharuddin, Ruhul Izzati; Wan Sulaiman, Wan Syibrah Hanisah; Mohd Latiff, Nur Hanie (AESS PUBLICATIONS, 2020)
Water pollution and water scarcity due to the discharge of untreated domestic and industrial wastewater into aquatic bodies need serious attention. A number of physical, chemical, and biological methods have been developed for wastewater treatment; among these, the use of cyanobacteria is considered as sustainable ways of averting the consequences. The dual application of microalgae for phycoremediation and biomass production for value products like biofuels and fertilizers is a feasible and eco-friendly alternative. This research aimed to investigate variables controlling heavy metal sequestration mechanism by assessing the effects of environmental variables from the mixtures of artificial wastewater samples using Synechococcus sp., and Pseudanabaena sp. Six heavy metals (Pb, Fe, Cr, Cd, Al, and Cu) treatments were tested and analyzed by Inductively Coupled Plasma (ICP) at three different periods of time (week 1 until week 3). The results indicated that both cyanobacteria species have equal potential to sequester heavy metals. However, Pseudanabaena sp. is the best phycoremediator agent due to substantial high Bio-concentration factor (BCF) compared to Synechococcus sp. On top of that, a regulatory step for the cyanobacteria cell growth and production mechanism is mediated by pH.